Soft tissue myxofibrosarcoma: A clinico‐pathological analysis of a series of 75 patients with emphasis on the epithelioid variant. Issue 1 (13th April 2016) - Scoccianti, Guido; Ranucci, Valentina; Frenos, Filippo; Greto, Daniela; Beltrami, Giovanni; Capanna, Rodolfo; Franchi, Alessandro
Abstract : Background and Objectives: The clinical course of soft tissue myxofibrosarcoma is characterized by a high incidence of recurrences and there is no agreement on how to identify patients at major risk. An epithelioid histological variant has been described, with a possible worse prognosis. We reviewed our series to identify prognostic factors and assess clinical significance of the epithelioid variant. Methods: We examined the clinico‐pathological features of a series of 75 patients affected by soft tissue myxofibrosarcoma at a mean follow‐up of 63 months (range 17–132). Results: Disease specific survival and local recurrence free survival were, respectively, 84.8% and 76.8% at 5 years. Seven patients (8.6%) presented with the epithelioid variant with a survival of 62.5%. High grade and epithelioid morphology were negative prognostic factors for patient survival, high grade, and inadequate surgical margins for local recurrence. Radiotherapy had a local protective effect in high grade tumors. Conclusions: Our experience confirms the difficulties in obtaining wide margins in myxofibrosarcoma and the high rate of recurrence. Local recurrences did not significantly affect survival and a limb‐sparing approach can be chosen also in recurrences. Patients affected by the epithelioid variant showed a worse prognosis. Chemotherapy should be considered as adjuvant treatment in this subtype. J. Surg. Oncol. 2016;114:50–55 . © 2016 Wiley Periodicals, Inc.